Evaluasi Pembelajaran Pendidikan Pancasila Dan Kewarnegaraan Melalui Pendekatan Saintifik - Febby Ontryna Limbong; Rasmita Pasaribu; Syahrial Syahrial (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
This research aims to investigate various aspects including teachers' comprehension of the learning process, its application in teaching, outcomes assessment, obstacles encountered by teachers in teaching, and strategies to address these hindrances when implementing Pancasila and citizenship education using a scientific approach in elementary schools. This study adopts an evaluation research methodology employing mixed methods, drawing from the Facial Expression Evaluation Model and Sequential Exploratory Design. Data collection techniques encompass interviews, questionnaires, observation, and documentation. The findings of the research indicate that: (1) PPKn teachers exhibit a strong understanding of the scientific approach, with 66.66% categorized as highly proficient. (2) The implementation of the scientific approach in elementary schools is highly commendable, with 74.92% falling into the high proficiency category. (3) Student performance and teacher efficacy in PPKn learning at the elementary level are deemed highly satisfactory. Teacher efficacy, measured by student learning outcomes, stands at 66.66%, indicating excellent performance. (4) Teachers perceive minimal obstacles in implementing the scientific approach. (5) Efforts made by teachers to address obstacles encountered in implementing the scientific approach are highly commendable.